CRITICAL REVIEW OF SYSTEM METHODOLOGY - Adisty Shabrina Nurqamarani (LPPM University 17 Agustus 1945 Samarinda, 2017)
This article contains critical review of system methodology. The aim was to explore different types of system methodology and its implication on management. The background of this article is due to the use of system methodology that is assumed beneficial to tackle management problem. A review of research articles that examined the variety of system methodology includes lean system methodology and system of system methodology is presented in this paper. The review suggests that implementation of system methodology should embrace a unitary purpose and control in order to be effective. As recommendations of the implementation of system methodology, managers and leaders may improve their employees’ performance by considering and addressing the aspects that affect the implementation on system methodology to be succeeds.